Preparation and Microstructural Characterization of Niobium Pentoxide Doped Barium Strontium Titanate Glass and Glass-Ceramics. Issue 1 (2nd January 2017) - Barkey, Bijay Kumar; Das, Swonal Sitam; Meher, Avinash; Saha, Partha
ABSTRACT: (Ba0.2 Sr0.8 )TiO3 -2SiO2 -B2 O3 -K2 O compositions based glass and glass-ceramics with and without 0.1 mol% Nb2 O5 were prepared by melt-quench method. XRD and FTIR spectra reveal the formation of amorphous structure and the presence of stretching and deformation vibration bonds of B-O-Si linkage and Si-O-Si bridges, respectively. Differential scanning calorimetry (DSC) of the glass sample shows that onset of crystallization for (Ba0.2 Sr0.8 )TiO3 phase occurs between ∼750 o and 800°C. XRD confirms the formation of (Ba0.25 6Sr0.744 )TiO3 as major phase upon controlled crystallization of the glass samples at ∼750 o -800°C for 3 h with rutile and SiO2 as minor phase(s). Quantitative phase analysis using structural Rietveld refinement of the powder XRD patterns shows that 0.1 mol% Nb2 O5 addition in the [(Ba0.2 Sr0.8 )O.TiO2 ]-[2SiO2 -B2 O3 ]- [K2 O] glass-ceramic system promotes the formation of Ba0.256 Sr0.744 TiO3 phase and suppresses the amount of rutile or TiO2 compared to undoped glass-ceramic system. SEM-EDS microstructural analysis of undoped glass-ceramic illustrates the formation of micrometer size flower-like Ba0.256 Sr0.744 TiO3, and needle-shape TiO2 crystals. However, addition of 0.1 mol% Nb2 O5 changes the crystals to irregular shape. Results from the dielectric measurements performed from room temperature to 250°C show that dielectric constant increases slightly with the addition of 0.1 mol% Nb2 O5 compared to undoped glass-ceramic samples. GRAPHICAL ABSTRACT: